The Efforts to Improve Maharah Qira’ah Mubtadi’in with The Implementation of Syllabic Method for The Tenth Grade Students at MA YPKL KEPRI: The Efforts to Improve Maharah Qira’ah Mubtadi’in with The Implementation of Syllabic Method for The Tenth Grade Students at MA YPKL KEPRI - Rizcy Fuzielestari, Syarifah; Akzam, Ismail; Alfitri ((الطموحات ) EL-THUMUHAT, 2022)
This study aims to investigate the implementation of Syllabic Method to improve the maharah qira'ah for the tenth grade students at MA YPKL KEPRI. The type of this study is action research conducted in the classroom, or classroom action research (CAR). The population of this study is all students at the tenth grade of MA YPKL KEPRI, and the sample of this study is only students in one class consisting of 12 students. The data collection techniques used are tests and observations. The results of this study show that the Syllabic Method can improve the maharah qira'ah mubtadi'in of students at the tenth grade of MA YPKL KEPRI. This increase can be seen from the results of the reading test at the first cycle which is 58.33%, and keep increasing to 91.67% at the second cycle. Keywords: Maharah Qira’ah, Maharah Qira'ah Mubtad'in, Syllabic Method